FORMATION OF MARKETING POLICY OF ENTERPRISES UNDER MARTIAL LAW - SAVYTSKA, Nataliia; BUBENETS, Iryna; ZAKOVOROTNY, Ivan; IGNATENKO, Oryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the disclosure of the key areas and tools for forming the marketing policy of enterprises in wartime. Strategic tools of marketing policy aimed at the long-term development of an enterprise remain relevant, and tactical tools are used to respond quickly to changes. The results of the research show that the work of manufacturing enterprises under martial law was most significantly affected by problems with supply, sales, and a lack of qualified workers. With restrictions on physical contacts and movement, digital channels are becoming the main channel of communication and sometimes sales. Businesses can actively use social media, contextual advertising, direct marketing, and other online tools to promote their products and services.Creating high-quality and informative content helps businesses prove their expertise, attract the attention of the audience, and strengthen their reputation. Blogs, articles, video content, and other formats can be effective tools in times of war. With the growing number of mobile device users, the development of mobile applications, optimization of websites for mobile devices and the use of mobile advertising allow you to reach your audience anytime, anywhere. In times of war and crisis, the focus on the local community and market becomes even more important. Businesses in relocation use local media channels, organize events and promotions for the local audience. Social media can be an effective tool for communicating with the audience, expressing the company's position on important issues, and supporting humanitarian and social initiatives.In such conditions, marketing policy is an effective tool for resilience, flexibility and readiness for rapid changes to ensure the development of the enterprise.
Keywords: marketing policy; enterprise; resilience; business development; competitiveness